1998
DOI: 10.1007/s004420050616
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratios in field populations of two parasitoids (Hymenoptera: Chalcidoidea) of Coccus hesperidum L. (Homoptera: Coccidae)

Abstract: We tested several assumptions and predictions of host-quality-dependent sex allocation theory (Charnov et al. 1981) with data obtained for the parasitoid Metaphycus stanleyi Compere on its host, brown soft scale (Coccus hesperidum L.), in a California citrus grove and in the laboratory. Scales ceased growing after parasitization by M. stanleyi. Thus, M. stanleyi may gauge host quality (=size) at oviposition. Host size positively influenced adult parasitoid size, and parasitoid size in turn influenced adult lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
5
26
0
Order By: Relevance
“…5) as hosts, as proposed by Bernal et al (1999a), albeit only for male offspring production. This is consistent with the results of Lampson et al (1996) and Bernal et al (1998Bernal et al ( , 1999b, which suggested that Metaphycus spp. use hosts of marginal size mostly for male offspring production.…”
Section: Discussionsupporting
confidence: 95%
“…5) as hosts, as proposed by Bernal et al (1999a), albeit only for male offspring production. This is consistent with the results of Lampson et al (1996) and Bernal et al (1998Bernal et al ( , 1999b, which suggested that Metaphycus spp. use hosts of marginal size mostly for male offspring production.…”
Section: Discussionsupporting
confidence: 95%
“…It is not currently established in California although it has been previously imported and released in the state (Kennett et al, 1995;Bernal, unpubl. Metaphycus stanleyi is also an internal parasitoid of various soft scales, including brown soft, citricola, and black scales (Annecke, 1964;Bernal et al, 1998). Metaphycus stanleyi is also an internal parasitoid of various soft scales, including brown soft, citricola, and black scales (Annecke, 1964;Bernal et al, 1998).…”
Section: Natural Historiesmentioning
confidence: 99%
“…data). It was imported to California from South Africa in 1937 for release against black scale (Bartlett, 1978), and is currently widely distributed within the state (Bartlett, 1953;Lampson & Morse, 1992;Bernal et al, 1998). It was imported to California from South Africa in 1937 for release against black scale (Bartlett, 1978), and is currently widely distributed within the state (Bartlett, 1953;Lampson & Morse, 1992;Bernal et al, 1998).…”
Section: Natural Historiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A. melinus is considered the main biotic mortality factor of A. aurantii in Italy (Lizzio et al 1998) and it is currently used in biological control programs by means of augmentative releases (Tumminelli et al 2000;Mazzeo et al 2004;Zappalà et al 2008); C. lycimnia and other species of the same genus are among the most common parasitoids of soft scales of economic importance all over the Mediterranean basin (Walter 1988;Bernal et al 1998); L. dactylopii is the most widely used parasitoid of the Citrus mealybug by means of inoculative releases.…”
Section: Introductionmentioning
confidence: 99%